2023
DOI: 10.1021/acsnano.3c03500
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Dendrite Growth and Side Reactions via Mechanically Robust Laponite-Based Electrolyte Membranes for Ultrastable Aqueous Zinc-Ion Batteries

Abstract: The development of aqueous zinc-ion batteries (AZIBs) faces significant challenges because of waterinduced side reactions arising from the high water activity in aqueous electrolytes. Herein, a quasi-solid-state electrolyte membrane with low water activity is designed based on a laponite (LP) nanoclay for separator-free AZIBs. The mechanically robust LP-based membrane can perform simultaneously as a separator and a quasi-solidstate electrolyte to inhibit dendrite growth and water-induced side reactions at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…19 Meanwhile, a peak at 10.9° emerged when the discharge reached 0.4 V (point C), which may belong to Zn x (CF 3 SO 3 ) y (OH) 2 x – y · n H 2 O (ZFH) resulting from the insertion of H + into the host material. 47,48 The intensity of the peak reached its maximum in the fully discharged state (point D) and progressively weakened and vanished during the charging process, demonstrating the reversible H + insertion/extraction behavior in the electrode. The above results suggested that the MoS 1.8 Se 0.2 /rGO cathode underwent an H + /Zn 2+ co-insertion/extraction process during discharging/charging.…”
Section: Resultsmentioning
confidence: 95%
“…19 Meanwhile, a peak at 10.9° emerged when the discharge reached 0.4 V (point C), which may belong to Zn x (CF 3 SO 3 ) y (OH) 2 x – y · n H 2 O (ZFH) resulting from the insertion of H + into the host material. 47,48 The intensity of the peak reached its maximum in the fully discharged state (point D) and progressively weakened and vanished during the charging process, demonstrating the reversible H + insertion/extraction behavior in the electrode. The above results suggested that the MoS 1.8 Se 0.2 /rGO cathode underwent an H + /Zn 2+ co-insertion/extraction process during discharging/charging.…”
Section: Resultsmentioning
confidence: 95%
“…This indicated that SG molecules were chemically stable and remained effective during charge/discharge. 34,35 Fig. 5b depicts the rate performance of the full cells at current densities ranging from 0.1 to 5 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…5a, due to the fact that there are few free water molecules and a large amount of polar hydroxyl groups (˙OH) in the PVA gel, it can effectively combine with dissolved Mn 2+ ions through coordination and exhibit a strong interaction. 55,56 To a certain extent, this obviously slows the chemical dissolution of Mn substance and thus improves the device cycle life. The capacitance retention rate can reach 91% after 5000 cycles (refer to Fig.…”
Section: Resultsmentioning
confidence: 99%